Submerged on the surface: the not-so-hidden Jews of Nazi Berlin, 1941-1945 - Lutjens, Richard (Berghahn, 2019)
"Between 1941 and 1945, thousands of German Jews, in fear for their lives, made the choice to flee their impending deportations and live submerged in the shadows of the Nazi capital. Drawing on a wealth of archival evidence and interviews with survivors, this book reconstructs the daily lives of Jews who stayed in Berlin during the war years. Contrary to the received wisdom that "hidden" Jews stayed in attics and cellars and had minimal contact with the outside world, the author reveals a cohort of remarkable individuals who were constantly on the move and actively fought to ensure their own survival."--